A sodium-replenishing method for sodium-ion battery and sodium-replenished sodium-ion battery

Through the two-step sodium supplementation method, the uniform dispersion of sodium salt and coal-based hard carbon materials in sodium ion batteries and the density of SEI films are achieved, which solves the problems of insufficient performance attenuation and stability caused by impurities in sodium ion batteries, and improves the charging and discharging efficiency and service life of the battery.

CN119764592AActive Publication Date: 2025-04-04GUOKE TANMEI NEW MATERIALS (HUZHOU) CO LTD +2
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510273595.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-10
Publication Date
2025-04-04
Estimated Expiration
2045-03-10

AI Technical Summary

Technical Problem

In existing sodium ion batteries, most impurities in hard charcoal materials cause attenuation of the material's performance, low first-term efficiency, and insufficient performance stability during recycling of the battery.

Method used

The two-step sodium supplementation method is adopted to disperse the sodium salt and the coal-based hard carbon negative electrode material evenly through slurry dispersion, increase the platform capacity and stabilize the platform area potential, and spray sodium supplementation liquid to the surface of the electrode sheet to increase the density of the SEI film, reduce the loss of sodium ions, and optimize the transmission path and kinetic process of sodium ions.

Benefits of technology

It improves the charging and discharging speed and efficiency of sodium ion batteries in the slope area, extends the service life of the battery, and avoids the damage to electrode structure and performance degradation caused by excessive prenatination.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764592A_ABST
    Figure CN119764592A_ABST
Patent Text Reader

Abstract

The present invention provides a sodium replenishment method for a sodium ion battery and a sodium ion battery after sodium replenishment, belonging to the technical field of sodium ion batteries. The sodium replenishment method comprises the following steps: mixing a stabilizer, a sodium salt and a solvent to obtain a sodium replenishment solution, and dividing the sodium replenishment solution into two parts; mixing a coal-based hard carbon negative electrode material, a conductive glue, a first portion of the sodium replenishment solution and a binder to obtain a mixed slurry, coating the mixed slurry on a current collector to obtain a negative electrode plate; cold rolling the negative electrode plate once, then spraying the second portion of the sodium replenishment solution, and then hot rolling a second time to obtain a sodium replenished negative electrode plate; assembling the sodium replenished negative electrode plate with a positive electrode plate, an electrolyte and a diaphragm, and then performing pre-sealing aging and formation treatment, and encapsulating and forming. The present invention solves the defects of performance attenuation and low first efficiency caused by many impurities in coal-based hard carbon negative electrode materials, optimizes the plate structure and ion transmission channels, improves the capacity of the platform area and the slope area, and also improves the battery energy density and service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sodium ion batteries, and in particular relates to a method for replenishing sodium in a sodium ion battery and a sodium ion battery after replenishing sodium. Background Art

[0002] Sodium-ion batteries have a similar energy storage mechanism to lithium-ion batteries, and sodium resources are abundant and low in cost. Therefore, they are expected to replace lithium-ion batteries and be widely used in large-scale energy storage fields.

[0003] Hard carbon materials are considered to be a highly commercially valuable negative electrode material for sodium-ion batteries. However, the raw coal used to prepare them contains impurities such as ash. Although it can be deashed by acid washing and other methods, it is difficult to completely remove the impurities. The residual impurities may have an adverse effect on the sodium storage performance of the battery, and also cause the materials after pyrolysis to be different in terms of graphitization degree, carbon layer spacing and surface chemical composition, thus bringing difficulties to the optimization of electrochemical performance. In addition, the performance stability of coal-based hard carbon negative electrodes needs to be improved during the long-term cycle use of batteries.

[0004] To this end, researchers have proposed a pre-sodiumization method to solve the above problems. Currently, the common pre-sodiumization methods for sodium-ion batteries are mainly the following: in-situ doping pre-sodiumization, electrochemical pre-sodiumization, chemical pre-sodiumization and contact pre-sodiumization. Among them, the contact pre-sodiumization method is to directly contact the metal sodium sheet with the negative electrode of the battery for pre-sodiumization, infiltrate the interface between the sodium sheet and the negative electrode with electrolyte, and adjust the contact pressure between the sodium sheet and the negative electrode by applying external force, thereby controlling the depth and uniformity of the pre-sodiumization. This method is conducive to controlling the degree of pre-sodiumization of the electrode, but its production process conditions are relatively high and it is not easy to scale up.

[0005] Therefore, how to effectively avoid the defects of material performance degradation and low initial efficiency caused by excessive impurities in hard carbon materials, optimize the electrode structure and ion transmission channels, further increase the capacity of the platform area and slope area, and improve the battery energy density and service life, is a technical problem that needs to be solved urgently. Summary of the invention

[0006] In view of the deficiencies in the prior art, the object of the present invention is to provide a method for replenishing sodium in a sodium ion battery and a sodium ion battery after replenishing sodium. Starting from the perspective of battery system design, the present invention adopts a two-step sodium replenishment method for coordinated cooperation, which not only disperses the sodium salt and the coal-based hard carbon negative electrode material evenly through slurry dispersion to increase the platform capacity and stabilize the platform area potential, but also sprays the sodium replenishment solution onto the surface of the electrode to increase the density of the SEI film, thereby reducing the loss of sodium ions in the positive electrode and the electrolyte, improving the charging and discharging characteristics in the slope zone, optimizing the transmission path and kinetic process of sodium ions in the coal-based hard carbon negative electrode material, and increasing the ion diffusion rate in the slope zone, so that the sodium ion battery can be charged and discharged more quickly and efficiently in the slope zone. In addition, the two-step sodium replenishment method can also avoid the problems of electrode structure destruction and performance degradation caused by excessive pre-sodiumization.

[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a method for replenishing sodium in a sodium ion battery, the method comprising the following steps: (1) A stabilizer, a sodium salt and a solvent are mixed to obtain a sodium replenishing solution, and the sodium replenishing solution is divided into two parts.

[0008] (2) A coal-based hard carbon negative electrode material, a conductive glue, a first portion of a sodium replenishing solution and a binder are mixed to obtain a mixed slurry, and then the mixed slurry is coated on a current collector to obtain a primary sodium replenishing negative electrode sheet.

[0009] (3) The primary sodium-supplemented negative electrode sheet is subjected to a cold roll pressing, and then a second portion of the sodium-supplementing liquid is sprayed on the surface of the negative electrode sheet, followed by a second hot roll pressing to obtain a secondary sodium-supplemented negative electrode sheet.

[0010] (4) Assembling the secondary sodium supplemented negative electrode plate with the positive electrode plate, electrolyte and separator, and then performing pre-sealing aging and formation treatment, and packaging and molding.

[0011] From the perspective of battery system design, the present invention adopts a two-step sodium supplementation method for coordinated cooperation. The sodium salt and the coal-based hard carbon negative electrode material are evenly dispersed by slurry dispersion to increase the platform capacity and stabilize the platform area potential, and the density of the SEI film is increased by spraying the sodium supplementation solution onto the surface of the pole piece, thereby reducing the loss of sodium ions in the positive electrode and the electrolyte, improving the slope area charge and discharge characteristics, optimizing the transmission path and kinetic process of sodium ions in the coal-based hard carbon negative electrode material, and increasing the ion diffusion rate in the slope area, so that the sodium ion battery can be charged and discharged more quickly and efficiently in the slope area. In addition, the two-step sodium supplementation method can also avoid the problems of electrode structure destruction and performance degradation caused by excessive pre-sodiumization.

[0012] The present invention uses a rolling process to make the coal-based hard carbon negative electrode material and the sodium salt more densely stacked, thereby increasing the density of the electrode, improving the conductivity of the electrode, and optimizing the structure and porosity of the electrode. At the same time, during the subsequent formation process, the ionized sodium ions can play a role inside and on the surface of the electrode, making the capacity more stable and less "dead sodium" formed.

[0013] The present invention adopts two-step sodium supplementation to avoid excessive pre-sodiumization that may lead to electrode structure damage and performance degradation.

[0014] Preferably, the stabilizer in step (1) comprises any one of vinylene carbonate, ethylene carbonate, propylene carbonate, fluoroethylene carbonate, 1,3-propane sultone or vinyl sulfite, or a combination of at least two thereof.

[0015] Preferably, the sodium salt in step (1) comprises any one of sodium bis(fluorosulfonyl)imide, sodium perchlorate, sodium hexafluorophosphate or a boron-containing sodium salt, or a combination of at least two thereof.

[0016] Preferably, the solvent in step (1) comprises water.

[0017] Preferably, the components in the sodium supplement solution of step (1) include, by mass content: 0.5-30% of stabilizer, for example, 0.5%, 1%, 5%, 10%, 15%, 20%, 25% or 30%, etc., 0.5-70% of sodium salt, for example, 0.5%, 1%, 10%, 20%, 30%, 40%, 50%, 60% or 70%, etc., and the balance is solvent.

[0018] In the present invention, if the content of the stabilizer is too much, it will lead to slow ion migration and decreased conductivity, thereby affecting the battery rate performance, and will also lead to an increase in battery side reactions and poor cycle performance; if the content of the stabilizer is too little, the battery will have poor thermal stability and storage performance, and will be prone to safety problems. If the content of the sodium salt is too much, it will lead to accelerated growth of negative electrode dendrites, causing internal short circuits, and will also cause the pole piece to expand, gas production inside the battery to cause battery deformation, resulting in unstable SEI film, increased side reactions, low energy density, poor cycle performance, etc.

[0019] Preferably, the components in the sodium supplement solution of step (1) include, by weight, 0.5-5% of a stabilizer, 0.5-20% of a sodium salt, and the remainder being a solvent.

[0020] Preferably, the raw material for preparing the coal-based hard carbon negative electrode material in step (2) is coal-based material.

[0021] Preferably, the coal-based material includes any one of anthracite, lean coal, lean coal, coking coal, fat coal, gas coal, slightly sticky coal, non-sticky coal, long flame coal or lignite, or a combination of at least two of them, preferably long flame coal.

[0022] Preferably, the conductive adhesive in step (2) comprises a conductive agent, a thickener and a solvent.

[0023] Preferably, the conductive agent includes any one of carbon black, acetylene black, graphene or carbon nanotubes, or a combination of at least two of them.

[0024] Preferably, the thickener comprises sodium carboxymethylcellulose.

[0025] Preferably, based on the total mass of the conductive adhesive, the mass content of the conductive agent is 1-10%, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%, etc., and the mass content of the thickener is 0.5-2%, for example, 0.5%, 1%, 1.5% or 2%, etc.

[0026] Preferably, the solid content of the mixed slurry in step (2) is 30-70wt%, for example, 30wt%, 40wt%, 50wt%, 60wt% or 70wt%.

[0027] Preferably, based on the total weight of the mixed slurry in step (2), the content of the coal-based hard carbon negative electrode material is 70-96%, for example, 70%, 75%, 80%, 85%, 90%, 95% or 96%, etc., the content of the conductive agent is 0.5-20%, for example, 0.5%, 1%, 5%, 10%, 15% or 20%, etc., the content of the thickener is 0.5-5%, for example, 0.5%, 1%, 2%, 3%, 4% or 5%, etc., and the content of the binder is 0.5-10%, for example, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%, etc.

[0028] Preferably, in step (2), the mass of the stabilizer in the first sodium-supplementing solution accounts for 0.5-5% of the mass of the solvent in the first sodium-supplementing solution, for example, it may be 0.5%, 1%, 2%, 3%, 4% or 5%.

[0029] Preferably, the mass of the sodium salt in the first sodium replenishing solution in step (2) accounts for 0.05-5% of the mass of the coal-based hard carbon negative electrode material in the mixed slurry, for example, it can be 0.05%, 0.1%, 1%, 2%, 3%, 4% or 5%.

[0030] Preferably, the primary cold rolling in step (3) is performed to 60-80% of the designed compaction density, for example, 60%, 65%, 70%, 75% or 80%.

[0031] Preferably, the pressure of the cold rolling in step (3) is 1-100 MPa, for example, it can be 1 MPa, 5 MPa, 10 MPa, 20 MPa, 30 MPa, 40 MPa, 50 MPa, 60 MPa, 70 MPa, 80 MPa, 90 MPa or 100 MPa, and the temperature is 20-35°C, for example, it can be 20°C, 22°C, 24°C, 26°C, 28°C, 30°C, 32°C, 34°C or 35°C.

[0032] Preferably, the contents of the components of the second sodium-replenishing solution in step (3) and the first sodium-replenishing solution in step (2) are the same.

[0033] It should be noted that when spraying the second portion of sodium replenishing solution, 0.5-500 mg of sodium salt is used as the basis for every 1 kg of active substance. The spraying amount and spraying rate of the second portion of sodium replenishing solution are determined according to this ratio, the surface load of the coated electrode, the roller conveying speed and the formula of the sodium replenishing solution.

[0034] In the present invention, the spraying speed should match the designed surface load of the electrode and the roller conveying speed. If the spraying rate is too low, the sodium content of the electrode will be low; if the spraying rate is too high, the sodium content of the electrode in the local area will be high. The spraying speed is uneven, resulting in poor uniformity of the sodium supplementation density of the electrode, which will lead to uneven battery performance.

[0035] Preferably, the pressure of the secondary hot rolling in step (3) is 1-50 MPa, for example, 1 MPa, 5 MPa, 10 MPa, 20 MPa, 30 MPa, 40 MPa or 50 MPa, and the temperature is 50-150°C, for example, 50°C, 75°C, 100°C, 125°C or 150°C.

[0036] Preferably, the second hot rolling in step (3) is performed to a designed compaction density.

[0037] Preferably, the positive electrode plate in step (4) includes a current collector and a positive electrode active layer disposed on a surface of one side of the current collector.

[0038] It should be noted that the present invention does not limit the type of the positive electrode active layer. For example, the material of the positive electrode active layer can be a layered transition metal oxide, a polyanionic compound, or a Prussian blue-based positive electrode material. The current collector can be, for example, aluminum foil.

[0039] Preferably, the pre-sealing aging time in step (4) is 5-48 h, for example, it can be 5 h, 10 h, 15 h, 20 h, 25 h, 30 h, 35 h, 40 h, 45 h or 48 h.

[0040] Preferably, the chemical formation step in step (4) includes primary chemical formation and secondary chemical formation.

[0041] Preferably, the primary formation pressure is normal pressure, and the temperature is 40-85° C., for example, 40° C., 50° C., 60° C., 70° C. or 80° C. It should be noted that normal pressure refers to one atmosphere.

[0042] Preferably, the pressure of the secondary formation is 10-300 KPa, for example, it can be 10 KPa, 50 KPa, 100 KPa, 150 KPa, 200 KPa, 250 KPa or 300 KPa, and the temperature is 60-85°C, for example, it can be 60°C, 70°C, 80°C or 85°C.

[0043] Preferably, the sodium supplementation method comprises the following steps: (a) A stabilizer, a sodium salt and a solvent are mixed to prepare a sodium replenishing solution, and the sodium replenishing solution is divided into two parts; the components in the sodium replenishing solution include, by weight content: 0.5-30% of a stabilizer, 0.5-70% of a sodium salt, and the remainder being a solvent.

[0044] The conductive agent, thickener and solvent are mixed to prepare a conductive adhesive; based on the total mass of the conductive adhesive, the mass content of the conductive agent is 1-10%, and the mass content of the thickener is 0.5-2%.

[0045] (b) The coal-based hard carbon negative electrode material and the conductive glue are stirred and mixed, and then the first portion of the sodium replenishing solution is added and continued to be stirred and mixed, and then a binder is added and stirred and mixed and vacuum degassed to obtain a mixed slurry with a solid content of 30-70wt%, and then the mixed slurry is coated on the current collector aluminum foil, and after drying, a primary sodium replenishing negative electrode sheet is obtained.

[0046] Among them, based on the weight of the solid components in the mixed slurry, the content of the coal-based hard carbon negative electrode material is 70-96%, the content of the conductive agent is 0.5-20%, the content of the thickener is 0.5-5%, and the content of the binder is 0.5-10%; the mass of the stabilizer in the first sodium replenishment solution accounts for 0.5-5% of the mass of the solvent in the first sodium replenishment solution; the mass of the sodium salt in the first sodium replenishment solution accounts for 0.05-5% of the mass of the coal-based hard carbon negative electrode material in the mixed slurry.

[0047] (c) subjecting the primary sodium-supplemented negative electrode sheet to a primary cold rolling press to 60-80% of the designed compaction density, the primary cold rolling press having a pressure of 1-100 MPa and a temperature of 20-35°C, and then spraying a second portion of sodium-supplementing solution on the surface of the negative electrode sheet, wherein the second portion of sodium-supplementing solution has the same content of each component as the first portion of sodium-supplementing solution, followed by drying, and then subjecting the secondary hot rolling press to a designed compaction density, wherein the secondary hot rolling press has a pressure of 1-50 MPa and a temperature of 50-150°C, to obtain a secondary sodium-supplemented negative electrode sheet.

[0048] (d) Assembling the secondary sodium-supplemented negative electrode sheet, the positive electrode sheet and the separator to obtain a dry battery cell, which is then rolled, die-cut, tab-welded and injected with electrolyte, followed by 5-48h pre-sealing aging.

[0049] The aged battery cell is then subjected to a primary formation to 50-95% SOC (for example, 50% SOC, 55% SOC, 60% SOC, 65% SOC, 70% SOC, 75% SOC, 80% SOC, 85% SOC, 90% SOC or 95% SOC, etc.) in a normal pressure environment with low humidity (i.e., relative humidity less than 30%), at a temperature of 40-85°C, and is subjected to a secondary formation to 100% SOC after vacuum exhaust, wherein the pressure of the secondary formation is 10-300 KPa, the temperature is 60-85°C, and the current of the primary formation and the secondary formation are both 0.01-0.5C (for example, 0.01C, 0.1C, 0.2C, 0.3C, 0.4C or 0.5C).

[0050] After the formation is completed, the battery is packaged and then discharged to 0% SOC at a rate of 0.01-0.5C (for example, 0.01C, 0.1C, 0.2C, 0.3C, 0.4C or 0.5C) to obtain a sodium-supplemented sodium-ion battery.

[0051] In the present invention, discharging to 0% SOC at a rate of 0.01-0.5C can further optimize the negative electrode sodium insertion and extraction channels and storage sites, improve the stability of the electrode structure, and improve the balance of the internal system of the battery.

[0052] In a second aspect, the present invention provides a sodium-supplemented sodium ion battery, wherein the sodium-supplemented sodium ion battery is obtained by the sodium-supplementing method described in the first aspect.

[0053] It should be noted that the sodium ion battery obtained in the present invention can be a button-type, bean-type battery and a battery assembled by any one of the processes of cylindrical winding, square winding, square stacking, soft package winding, soft package stacking, etc.

[0054] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0055] Compared with the prior art, the present invention has the following beneficial effects: (1) From the perspective of battery system design, the present invention adopts a two-step sodium supplementation method for coordinated cooperation. The sodium salt and the coal-based hard carbon negative electrode material are evenly dispersed by slurry dispersion to increase the platform capacity and stabilize the platform area potential. The density of the SEI film is increased by spraying the sodium supplementation solution onto the surface of the electrode, thereby reducing the loss of sodium ions in the positive electrode and the electrolyte, improving the slope area charge and discharge characteristics, optimizing the sodium ion transmission path and kinetic process in the coal-based hard carbon negative electrode material, and increasing the ion diffusion rate in the slope area, so that the sodium ion battery can be charged and discharged more quickly and efficiently in the slope area. In addition, the two-step sodium supplementation method can also avoid the problems of electrode structure destruction and performance degradation caused by excessive pre-sodiumization.

[0056] (2) The present invention uses a roller pressing process to make the coal-based hard carbon negative electrode material and sodium salt more densely stacked, thereby increasing the density of the electrode, improving the conductivity of the electrode, and optimizing the structure and porosity of the electrode. At the same time, during the subsequent formation process, the ionized sodium ions can play a role inside and on the surface of the electrode, making the capacity more stable and less "dead sodium" formed. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] Figure 1 The process flow chart of the sodium supplementation method provided in Example 1 of the present invention.

[0058] Figure 2 This is the cycle curve of the sodium ion battery after sodium supplementation provided in Example 1 of the present invention.

[0059] Figure 3 This is a SEM image of the negative electrode plate after sodium supplementation provided in Example 1 of the present invention. DETAILED DESCRIPTION

[0060] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0061] Example 1 This embodiment provides a sodium supplementation method for a sodium ion battery, and its process flow chart is as follows: Figure 1 As shown, the sodium supplementation method comprises the following steps: (1) A stabilizer, a sodium salt and deionized water are mixed to prepare a sodium replenishing solution, and the sodium replenishing solution is divided into two parts; the components in the sodium replenishing solution include, by weight content: 15% of a stabilizer, 35% of a sodium salt, and the balance of deionized water.

[0062] A conductive agent, a thickener and deionized water are mixed to prepare a conductive adhesive; based on the total mass of the conductive adhesive, the mass content of the conductive agent is 5%, and the mass content of the thickener is 1%.

[0063] The stabilizer is vinylene carbonate, the sodium salt is sodium bis(fluorosulfonyl)imide, the conductive agent is carbon black, and the thickener is sodium carboxymethyl cellulose.

[0064] (2) The lump long flame coal is crushed, low-temperature carbonized to remove impurities, purified, pulverized and high-temperature carbonized in sequence to obtain a coal-based hard carbon negative electrode material, which is then stirred and mixed with a conductive glue, and then the first portion of the sodium replenishment solution is added and continued to be stirred and mixed, followed by adding a binder, stirring and mixing, and vacuum degassing to obtain a mixed slurry with a solid content of 50wt%, and then the mixed slurry is coated on a current collector aluminum foil and dried to obtain a primary sodium replenishment negative electrode sheet.

[0065] Among them, based on the weight of the solid components in the mixed slurry, the content of the coal-based hard carbon negative electrode material is 80%, the content of the conductive agent is 10%, the content of the thickener is 2%, and the content of the binder is 5%; the mass of the stabilizer in the first sodium replenishment solution accounts for 2.5% of the mass of the solvent in the first sodium replenishment solution; the mass of the sodium salt in the first sodium replenishment solution accounts for 2.5% of the mass of the coal-based hard carbon negative electrode material in the mixed slurry.

[0066] (3) The first sodium-supplemented negative electrode sheet is subjected to a cold roller pressing to 70% of the designed compaction density, the pressure of the first cold roller pressing is 30 MPa, and the temperature is 25°C, and then a second portion of sodium-supplementing solution is sprayed on the surface of the negative electrode sheet (the spraying rate is: the rate of 200 mg of sodium salt to 1 kg of active substance), the second portion of sodium-supplementing solution and the first portion of sodium-supplementing solution have the same content of each component, and then dried, and then a second hot roller pressing is performed to the designed compaction density, the pressure of the second hot roller pressing is 10 MPa, and the temperature is 100°C, to obtain a second sodium-supplemented negative electrode sheet.

[0067] (4) Assembling the secondary sodium-supplemented negative electrode plate, the positive electrode plate (including aluminum foil, and a positive electrode active layer disposed on one surface of the aluminum foil, wherein the material of the positive electrode active layer includes a polyanionic compound, Super P, CMC and SBR) and a separator (i.e., a polypropylene PP film) to obtain a dry battery cell, and then performing winding, die-cutting, tab welding and electrolyte injection (i.e., sodium hexafluorophosphate solution), followed by 24 hours of pre-sealing aging.

[0068] The aged battery cell is then subjected to a primary formation to 70% SOC at 60°C in a low humidity (i.e., 1% RH) and normal pressure environment, and then subjected to a secondary formation to 100% SOC after vacuum exhaust. The secondary formation pressure is 150 KPa, the temperature is 70°C, and the currents of the primary and secondary formations are both 0.3C.

[0069] After the formation is completed, the battery is packaged and then discharged to 0% SOC at a rate of 0.3C to obtain a sodium-supplemented sodium-ion battery.

[0070] Figure 2 The cycle curve of the sodium-ion battery after sodium supplementation provided in this embodiment is shown. It can be seen from the figure that after 200 cycles of the sodium-ion battery after sodium supplementation, the gram capacity has hardly decayed, and the capacity retention rate is close to 100%.

[0071] Figure 3 The SEM image of the negative electrode plate after sodium supplementation provided in this embodiment is shown. It can be seen from the image that the particle morphology after sodium supplementation has not changed and still shows an irregular particle distribution.

[0072] Example 2 This embodiment provides a method for replenishing sodium in a sodium ion battery, and the method comprises the following steps: (1) A stabilizer, a sodium salt and deionized water are mixed to prepare a sodium replenishing solution, and the sodium replenishing solution is divided into two parts; the components in the sodium replenishing solution include, by weight content: 10% of the stabilizer, 60% of the sodium salt, and the balance of deionized water.

[0073] A conductive agent, a thickener and deionized water are mixed to prepare a conductive adhesive; based on the total mass of the conductive adhesive, the mass content of the conductive agent is 1%, and the mass content of the thickener is 2%.

[0074] Wherein, the stabilizer is ethylene carbonate, the sodium salt is sodium perchlorate, the conductive agent is acetylene black, and the thickener is sodium carboxymethyl cellulose.

[0075] (2) The lump long flame coal is crushed, low-temperature carbonized to remove impurities, purified, pulverized and high-temperature carbonized in sequence to obtain a coal-based hard carbon negative electrode material, which is then stirred and mixed with a conductive glue, and then the first portion of the sodium replenishment solution is added and continued to be stirred and mixed, followed by adding a binder, stirring and mixing, and vacuum degassing to obtain a mixed slurry with a solid content of 30wt%, and then the mixed slurry is coated on a current collector aluminum foil, and dried to obtain a primary sodium replenishment negative electrode sheet.

[0076] Among them, based on the weight of the solid components in the mixed slurry, the content of the coal-based hard carbon negative electrode material is 70%, the content of the conductive agent is 15%, the content of the thickener is 5%, and the content of the binder is 1%; the mass of the stabilizer in the first sodium-replenishing solution accounts for 1% of the mass of the solvent in the first sodium-replenishing solution; the mass of the sodium salt in the first sodium-replenishing solution accounts for 5% of the mass of the coal-based hard carbon negative electrode material in the mixed slurry.

[0077] (3) The first sodium-supplemented negative electrode sheet is subjected to a cold roller pressing to 60% of the designed compaction density, the pressure of the first cold roller pressing is 20 MPa, and the temperature is 25°C, and then a second portion of sodium-supplementing solution is sprayed on the surface of the negative electrode sheet (spraying rate meter: the rate of 200 mg sodium salt to 1 kg active substance), the second portion of sodium-supplementing solution and the first portion of sodium-supplementing solution have the same content of each component, and then dried, and then a second hot roller pressing is performed to the designed compaction density, the pressure of the second hot roller pressing is 10 MPa, and the temperature is 50°C, to obtain a second sodium-supplemented negative electrode sheet.

[0078] (4) Assembling the secondary sodium-supplemented negative electrode plate, the positive electrode plate (including aluminum foil, and a positive electrode active layer disposed on one surface of the aluminum foil, wherein the material of the positive electrode active layer includes a polyanionic compound, Super P, CMC and SBR) and a separator (i.e., a PP film) to obtain a dry battery cell, and then performing winding, die-cutting, tab welding and electrolyte injection (i.e., sodium hexafluorophosphate solution), followed by 12 hours of pre-sealing aging.

[0079] The aged battery cell is then subjected to a primary formation to 50% SOC at a temperature of 85°C in a low humidity (i.e., 1% RH) and normal pressure environment, and then subjected to a secondary formation to 100% SOC after vacuum exhaust. The secondary formation pressure is 300 KPa, the temperature is 85°C, and the currents of the primary and secondary formations are both 0.1C.

[0080] After the formation is completed, the battery is packaged and then discharged to 0% SOC at a rate of 0.1C to obtain a sodium-supplemented sodium-ion battery.

[0081] Example 3 This embodiment provides a method for replenishing sodium in a sodium ion battery, and the method comprises the following steps: (1) A stabilizer, a sodium salt and deionized water are mixed to prepare a sodium replenishing solution, and the sodium replenishing solution is divided into two parts; the components in the sodium replenishing solution include, by weight content: 30% of a stabilizer, 10% of a sodium salt, and the balance of deionized water.

[0082] A conductive agent, a thickener and deionized water are mixed to prepare a conductive adhesive; based on the total mass of the conductive adhesive, the mass content of the conductive agent is 10%, and the mass content of the thickener is 1%.

[0083] The stabilizer is fluoroethylene carbonate, the sodium salt is sodium hexafluorophosphate, the conductive agent is carbon nanotubes, and the thickener is sodium carboxymethyl cellulose.

[0084] (2) The lump long flame coal is crushed, low-temperature carbonized to remove impurities, purified, pulverized and high-temperature carbonized in sequence to obtain a coal-based hard carbon negative electrode material, which is then stirred and mixed with a conductive glue, and then the first portion of the sodium replenishment solution is added and continued to be stirred and mixed, followed by adding a binder, stirring and mixing, and vacuum degassing to obtain a mixed slurry with a solid content of 70wt%, and then the mixed slurry is coated on a current collector aluminum foil, and dried to obtain a primary sodium replenishment negative electrode sheet.

[0085] Among them, based on the weight of the solid components in the mixed slurry, the content of the coal-based hard carbon negative electrode material is 96%, the content of the conductive agent is 0.5%, the content of the thickener is 0.5%, and the content of the binder is 0.5%; the mass of the stabilizer in the first sodium replenishment solution accounts for 5% of the mass of the solvent in the first sodium replenishment solution; the mass of the sodium salt in the first sodium replenishment solution accounts for 5% of the mass of the coal-based hard carbon negative electrode material in the mixed slurry.

[0086] (3) The first sodium-supplemented negative electrode sheet is subjected to a cold roller pressing to 80% of the designed compaction density, the pressure of the first cold roller pressing is 10 MPa, and the temperature is 25°C, and then a second portion of sodium-supplementing solution is sprayed on the surface of the negative electrode sheet (spraying rate meter: the rate of 200 mg sodium salt to 1 kg active substance), the second portion of sodium-supplementing solution and the first portion of sodium-supplementing solution have the same content of each component, and then dried, and then a second hot roller pressing is performed to the designed compaction density, the pressure of the second hot roller pressing is 5 MPa, and the temperature is 150°C, to obtain a second sodium-supplemented negative electrode sheet.

[0087] (4) Assembling the secondary sodium-supplemented negative electrode plate, the positive electrode plate (including aluminum foil, and a positive electrode active layer disposed on one surface of the aluminum foil, wherein the material of the positive electrode active layer includes a polyanionic compound, Super P, CMC and SBR) and a separator (i.e., a PP film) to obtain a dry battery cell, and then performing winding, die-cutting, tab welding and electrolyte injection (i.e., sodium hexafluorophosphate solution), followed by 48 hours of pre-sealing aging.

[0088] The aged battery cell is then subjected to a primary formation to 95% SOC at a temperature of 40°C in a low humidity (i.e., 1% RH) and normal pressure environment, and then subjected to a secondary formation to 100% SOC after vacuum exhaust. The secondary formation pressure is 50 KPa, the temperature is 60°C, and the currents of the primary and secondary formations are both 0.5C.

[0089] After the formation is completed, the battery is packaged and then discharged to 0% SOC at a rate of 0.5C to obtain a sodium-supplemented sodium-ion battery.

[0090] Example 4 The difference between this embodiment and embodiment 1 is that the content of the stabilizer in the sodium supplement solution in step (1) is 40%.

[0091] The rest of the preparation methods and parameters were the same as those in Example 1.

[0092] Example 5 The difference between this embodiment and embodiment 1 is that the content of sodium salt in the sodium supplement solution in step (1) is 80%.

[0093] The rest of the preparation methods and parameters were the same as those in Example 1.

[0094] Example 6 The difference between this embodiment and embodiment 1 is that the spraying rate of the second sodium supplement solution in step (3) is recorded as: the rate of 50 mg sodium salt to 1 kg active substance. The rest of the preparation method and parameters are the same as those in embodiment 1.

[0095] Example 7 The difference between this embodiment and embodiment 1 is that the spraying rate of the second sodium supplement solution in step (3) is recorded as: the rate of 500 mg sodium salt to 1 kg active substance.

[0096] The rest of the preparation methods and parameters were the same as those in Example 1.

[0097] Comparative Example 1 The difference between this embodiment and embodiment 1 is that the second portion of sodium supplement solution is not sprayed.

[0098] The rest of the preparation methods and parameters were the same as those in Example 1.

[0099] Performance Testing The sodium ion batteries after sodium supplementation obtained in the above embodiments and comparative examples were subjected to first efficiency calculation and rate performance test. The test conditions of rate performance included: 1.5-3.5V, 0.2C discharge, and charging tests of 0.2C, 0.5C, 1C, 2C, 5C, 10C, and 0.2C in sequence.

[0100] The test results are shown in Table 1.

[0101] Table 1

[0102] analyze: As can be seen from the above table, the present invention adopts a two-step sodium supplementation method to cooperate with each other, increase the platform capacity and stabilize the platform area potential, increase the density of the SEI film, and optimize the transmission path and kinetic process of sodium ions in the coal-based hard carbon negative electrode material. In addition, the two-step sodium supplementation method can also avoid the problem of electrode structure destruction and performance degradation caused by excessive pre-sodiumization.

[0103] It can be seen from Examples 1 and 4-5 that if the content of the stabilizer is too much, it will be detrimental to ion migration, thereby affecting the battery rate performance, and will also lead to an increase in battery side reactions, and poor rate and cycle performance; if the content of the sodium salt is too much, it will be detrimental to the formation of the SEI film, increase side reactions, and poor energy density.

[0104] It can be seen from Example 1 and Examples 6-7 that if the spraying rate is too low, it will be unfavorable for the adsorption of sodium salt on the electrode, resulting in too little sodium supplementation; if the spraying rate is too high, it will be unfavorable for improving the coulombic efficiency of the battery cell, and the increase in sodium salt will lead to increased side reactions, reduced first efficiency, and increased electrode expansion rate, which will further affect the safety of the battery.

[0105] It can be seen from Example 1 and Comparative Example 1 that if only one step of sodium supplementation is performed, it will be detrimental to the improvement of the first efficiency of the battery. Compared with two-step sodium supplementation, while the SEI film is formed on the surface of the negative electrode, the amount of sodium supplementation in one step is limited, and the sodium salt consumption is relatively large. The two-step sodium supplementation can add more sodium salt to the surface of the electrode, reduce the interfacial impedance of the negative electrode surface when the SEI film is formed, and further improve the first efficiency of the battery.

[0106] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for replenishing sodium in a sodium ion battery, characterized in that: The sodium supplementation method comprises the following steps: (1) mixing a stabilizer, a sodium salt and a solvent to obtain a sodium replenishing solution, and dividing the sodium replenishing solution into two portions; (2) Mixing a coal-based hard carbon negative electrode material, a conductive glue, a first portion of a sodium replenishment solution and a binder to obtain a mixed slurry, and then coating the mixed slurry on a current collector to obtain a primary sodium replenishment negative electrode sheet; (3) cold rolling the primary sodium-supplemented negative electrode sheet, spraying a second portion of sodium-supplementing liquid on the surface of the negative electrode sheet, and then hot rolling a second time to obtain a secondary sodium-supplemented negative electrode sheet; (4) Assembling the secondary sodium supplemented negative electrode plate with the positive electrode plate, electrolyte and separator, and then performing pre-sealing aging and formation treatment, and packaging and molding.

2. The sodium supplementation method according to claim 1, characterized in that The stabilizer in step (1) comprises any one of vinylene carbonate, ethylene carbonate, propylene carbonate, fluoroethylene carbonate, 1,3-propane sultone or vinyl sulfite, or a combination of at least two thereof; And / or, the sodium salt in step (1) includes any one of sodium bis(fluorosulfonyl)imide, sodium perchlorate, sodium hexafluorophosphate or a boron-containing sodium salt, or a combination of at least two thereof; And / or, the solvent in step (1) includes water.

3. The sodium supplementation method according to claim 1, characterized in that The components in the sodium supplement solution of step (1) include, by weight, 0.5-30% of a stabilizer, 0.5-70% of a sodium salt, and the remainder being a solvent; Alternatively, the components in the sodium supplement solution of step (1) include, by weight, 0.5-5% of a stabilizer, 0.5-20% of a sodium salt, and the remainder being a solvent.

4. The sodium supplementation method according to claim 1, characterized in that The raw material for preparing the coal-based hard carbon negative electrode material in step (2) is coal-based material; The coal-based material includes any one of anthracite, lean coal, lean coal, coking coal, fat coal, gas coal, weakly sticky coal, non-sticky coal, long flame coal or lignite, or a combination of at least two thereof; And / or, the conductive adhesive in step (2) comprises a conductive agent, a thickener and a solvent; Based on the total mass of the conductive adhesive, the mass content of the conductive agent is 1-10%, and the mass content of the thickener is 0.5-2%.

5. The sodium supplementation method according to claim 4, characterized in that: The solid content of the mixed slurry in step (2) is 30-70wt%; And / or, based on the total weight of the mixed slurry in step (2), the content of the coal-based hard carbon negative electrode material is 70-96%, the content of the conductive agent is 0.5-20%, the content of the thickener is 0.5-5%, and the content of the binder is 0.5-10%; and / or, in step (2), the mass of the stabilizer in the first sodium-supplementing solution accounts for 0.5-5% of the mass of the solvent in the first sodium-supplementing solution; And / or, in step (2), the mass of the sodium salt in the first sodium replenishing solution accounts for 0.05-5% of the mass of the coal-based hard carbon negative electrode material in the mixed slurry.

6. The sodium supplementation method according to claim 1, characterized in that: Step (3) the primary cold rolling is performed to 60-80% of the designed compaction density; And / or, the pressure of the cold rolling in step (3) is 1-100 MPa and the temperature is 20-35°C; and / or, the contents of the components of the second sodium-replenishing solution in step (3) and the first sodium-replenishing solution in step (2) are the same; And / or, the pressure of the secondary hot roller pressing in step (3) is 1-50 MPa and the temperature is 50-150°C; And / or, the second hot rolling in step (3) is performed to a designed compaction density.

7. The sodium supplementation method according to claim 1, characterized in that: The positive electrode sheet in step (4) includes a current collector and a positive electrode active layer disposed on a surface of one side of the current collector; And / or, the pre-sealing aging time in step (4) is 5-48h; And / or, the chemical treatment step in step (4) includes primary chemical treatment and secondary chemical treatment; The pressure of the primary formation is normal pressure and the temperature is 40-85°C; The secondary formation has a pressure of 10-300 KPa and a temperature of 60-85°C.

8. The sodium supplementation method according to claim 1, characterized in that: The sodium supplementation method comprises the following steps: (a) mixing a stabilizer, a sodium salt and a solvent to prepare a sodium replenishing solution, and dividing the sodium replenishing solution into two parts; the components in the sodium replenishing solution include, by weight content: 0.5-30% of a stabilizer, 0.5-70% of a sodium salt, and the remainder being a solvent; The conductive agent, thickener and solvent are mixed to prepare a conductive adhesive; based on the total mass of the conductive adhesive, the mass content of the conductive agent is 1-10%, and the mass content of the thickener is 0.5-2%; (b) stirring and mixing the coal-based hard carbon negative electrode material and the conductive glue, then adding the first portion of the sodium supplement solution and continuing to stir and mix, then adding the binder and stirring and mixing and vacuum degassing to obtain a mixed slurry with a solid content of 30-70wt%, and then coating the mixed slurry on a current collector aluminum foil, and drying to obtain a primary sodium supplement negative electrode sheet; Wherein, based on the weight of the solid components in the mixed slurry, the content of the coal-based hard carbon negative electrode material is 70-96%, the content of the conductive agent is 0.5-20%, the content of the thickener is 0.5-5%, and the content of the binder is 0.5-10%; the mass of the stabilizer in the first sodium replenishment solution accounts for 0.5-5% of the mass of the solvent in the first sodium replenishment solution; the mass of the sodium salt in the first sodium replenishment solution accounts for 0.05-5% of the mass of the coal-based hard carbon negative electrode material in the mixed slurry; (c) subjecting the primary sodium-supplemented negative electrode sheet to a primary cold roller pressing to 60-80% of the designed compaction density, the primary cold roller pressing pressure being 1-100 MPa and the temperature being 20-35° C., and then spraying a second portion of sodium-supplementing solution on the surface of the negative electrode sheet, wherein the second portion of sodium-supplementing solution has the same content of each component as the first portion of sodium-supplementing solution, followed by drying, and then subjecting the secondary hot roller pressing to a designed compaction density, wherein the secondary hot roller pressing pressure is 1-50 MPa and the temperature is 50-150° C., to obtain a secondary sodium-supplemented negative electrode sheet; (d) assembling the secondary sodium-supplemented negative electrode sheet, the positive electrode sheet and the separator to obtain a dry battery cell, which is then rolled, die-cut, tab-welded and injected with electrolyte, followed by 5-48h pre-sealing aging; Then the aged battery cell is subjected to a primary formation to 50-95% SOC at a temperature of 40-85°C in a low humidity and normal pressure environment, and a secondary formation to 100% SOC after vacuum exhaust, wherein the pressure of the secondary formation is 10-300KPa, the temperature is 60-85°C, and the current of the primary formation and the secondary formation is 0.01-0.5C; After the formation is completed, the battery is packaged and then discharged to 0% SOC at a rate of 0.01-0.5C to obtain a sodium-supplemented sodium-ion battery.

9. A sodium-supplemented sodium ion battery, characterized in that: The sodium-supplemented sodium ion battery is obtained by the sodium-supplementing method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Negative electrode material, negative electrode plate and sodium ion battery

    CN115275191A

  • Sodium ion battery sodium supplement additive and method

    CN115275204A

  • Sodium ion negative plate, preparation method thereof and sodium ion battery

    CN115394967A

  • Sodium-ion battery negative electrode material, preparation method of negative electrode plate and sodium-ion battery

    CN116072994A